A collaborative expert literature review of pain education, assessment and management. (February 2012) - Schofield, Pat; Sofaer-Bennett, Beatrice; Hadjistavropoulos, Thomas; Zwakhalen, Sandra; Brown, Cary; Westerling, Dagmar; Weissbrod, Daniel; Škvarčč, Nevenka Krččevski; Wright, Shelagh
Pain assessment and management in older adults requires a special emphasis on the needs of this population, which is often not considered within general education. The purpose of this study was twofold: to determine the availability of education on pain in older adults around the world, and to present a review and synthesis of published guidelines and key papers on pain assessment and management in older adults. Following on from this study we intend to make recommendations on what work needs to be carried out in future to inform the development of a curriculum or curriculum content specifically dedicated to pain management for older adults. A discussion forum was set up through the Pain in Older Adults Special Interest Group of the International Association for the Study of Pain (IASP) at the end of 2009. This forum was initiated to determine the current level and availability of education available around the world for health professionals on pain in older adults. A number of IASP members from countries around the world participated in the discussion and identified educational courses on pain in older adults from their member country. Following on from this discussion, a number of leading experts agreed to collate guidelines and key papers and conduct a critical review using Appraisal of Guidelines Research and Evaluation (AGREE) criteria. A total of 14 guideline documents on pain assessment and management were reviewed by the group. The papers were reviewed and graded and then agreed between reviewers. From the guideline review, some recommendations can be made, but primarily, the key recommendation from this work was to develop collaboration and a review of key evidence on which future research may be developed so an educational focus may be highlighted. This article presents a summary of those documents along with recommendations for improved and consistent education informed by the guidelines currently developed, and consistent evidence-based assessment and management of chronic pain in older adults.